Evaluation of a Social Media Strategy to Promote Mental Health Literacy and Help-Seeking in Youth. Issue 1 (2nd January 2019) - Halsall, Tanya; Garinger, Christine; Dixon, Kaylyn; Forneris, Tanya
Abstract: In Canada, it is estimated that 15-21% of youth have at least one diagnosable mental illness and less than one third access the mental health services they need. Social media (SM) may present a unique opportunity to promote mental health for young people. mindyourmind, a web-facilitated program with a comprehensive SM presence, was designed to raise awareness of mental health issues and improve access to services for youth dealing with mental health concerns. This article presents an evaluation of their SM strategies with the intent to better understand their influence on youth mental health literacy (MHL) and help-seeking behavior.